Recommendations for the Development of Family-Based Interventions Aiming to Prevent Unhealthy Changes in Energy Balance-Related Behavior during the Transition to Parenthood: A Focus Group Study - Versele, Vickà; Deforche, Benedicte; Aerenhouts, Dirk; Clarys, Peter; Devlieger, Roland; Bogaerts, Annick; Liel, Christoph; Löchner, Johanna; Wolstein, Jörg; van Poppel, Mireille; Deliens, Tom (Nutrients, 2022)
Feasible interventions addressing unhealthy changes in energy balance-related behavior (EBRB) during pregnancy and early postpartum are needed. This study identified the needs and wishes of expecting and first-time parents concerning EBRB interventions during the transition to parenthood. Thirteen focus group discussions (n = 74) were conducted. Couples provided information about whether an intervention targeting unhealthy EBRB changes during pregnancy and postpartum would be acceptable, how such an intervention should look like, and in which way and during which period they needed support. Guided by the TiDIER checklist, all quotes were divided into five main categories (i.e., ‘what’, ‘how’, ‘when and how much’, ‘where’, ‘for and from whom’). Interventions should aim for changes at the individual, social, environmental and policy levels. The accessibility and approach (indirect or face-to-face) together with communicational aspects should be taken into account. A focus should go to delivering reliable and personalized information and improving self-regulation skills. Interventions should be couple-or family-based. Authorities, healthcare professionals, the partner and peers are important sources for intervention delivery and support. In the prevention of unhealthy EBRB changes around childbirth, the involvement of both parents is needed, while health care professionals play an important role in providing personalized advice.
CRIS-Team Scopus Importer:2024-11-26
Keywords: family-based; intervention strategy; needs assessment; nutrition; physical activity; postpartum; pregnancy; sedentary behavior